The impact of charismatic leadership on team performance: A study of sustainability of small and micro enterprises in China (International Journal of Management and Sustainability, 2025)
Small and micro enterprises (SMEs), serving as a major catalyst for economic and social advancement, play an irreplaceable role in promoting employment, technological innovation, and stimulating market vitality. Team performance is a key indicator for measuring the sustainable development level of SMEs, and the effectiveness of internal teams has a significant influence on determining their competitive standing and long-term development path. Charismatic leadership, as an important leadership style, is considered to have a unique role in motivating employees, promoting innovation, and facilitating team development through personal charm, influence, and appeal. This research centers on SMEs in China and explores how charismatic leadership affects team performance, particularly emphasizing the role played by team learning and team cohesion as intermediaries in this connection. The study gathered data via responses to a structured questionnaire completed by managers and employees within SMEs in Guangdong Province. The analysis shows that: (1) Charismatic leadership clearly enhances team performance in SMEs; (2) Team learning and team cohesion act as intermediaries through which charismatic leadership positively impacts team performance. The study clarifies the process through which charismatic leadership enhances team performance by fostering team learning and improving team cohesion, thereby not only enriching the theoretical framework regarding leadership behaviors and team effectiveness but also offering practical insights for SMEs to improve team performance and achieve sustainable development by cultivating charismatic leaders.